Muscle metabolism in response to oxidized fish oil feed in juvenile Nile tilapia - Xinyuan Li; Lili Chen; Hua Wen; Xuan Wang; Di Peng; Jianmin Zhang; Yangyang Liu; Ming Jiang; Lixue Dong; Feng Huang; Juan Tian (Water Biology and Security)
To investigate the effect of oxidized fish oil on fish muscle metabolic responses and flesh quality, Nile tilapia (Oreochromis niloticus) weighing 13.73 ​± ​0.31 ​g were fed two diets for 12 weeks: a fresh fish oil (FFO) and a highly oxidized fish oil (OFO) diet. The peroxide value of the FFO and OFO diets was 2.2 meq/kg and 120.6 meq/kg, respectively. The OFO diet resulted in a decrease in growth, muscularity, nutritional value of fatty acids in the muscle, and density of myofibers. In the OFO group, the mRNA expression levels of lipolysis genes including lipoprotein lipase (lpl) and hormone-sensitive lipase (hsl) in the muscle were upregulated compared with the FFO group, while, the mRNA expression level of acetyl CoA carboxylase was downregulated. Additionally, under the positive ion mode, the levels of DHA deposition in phosphatidylcholine and phosphatidyl ethanolamine were reduced in the muscle of the OFO group compared to the FFO group. A total of 68 proteins were identified in the muscle, of which 42 were up-regulated and 26 were down-regulated. The KEGG pathway enrichment analysis revealed that the major pathways of the differentially abundant proteins were the Wnt signaling pathway, TGF-beta signaling pathway, and proteoglycans in cancer. In summary, the OFO diet negatively affected growth, muscularity, and nutritional value. It also inhibited the transformation of myofiber types and led to the apoptosis of myofibers.